KUALITAS PELAYANAN PUBLIK PADA KANTOR CAMAT TABIR ULU KABUPATEN MERANGIN - Joko Susanto; Zepa Anggraini (Jurnal Administrasi Negara, 2019)
The delivery of public services is an attempt by the State to fulfill the basic needs and civil rights of every citizen of the goods, services, and administrative services provided by the public service providers. This study aims to determine how the quality of public service in subdistrict office tabir ulu merangin regency. Method This research uses descriptive research with a qualitative approach. Research data collection techniques by observation, interview and document review with informants totaling seven people. The results showed that the quality of public services in the Tabir Ulu Sub-District Office has not been well implemented overall, judging by the five dimensions of quality of public services, which are tangible, reliability, responsiveness, assurance, and empathy. Tangible, the waiting room is not yet equipped with air conditioning such as air conditioning, so that people do not feel comfortable in the waiting room. Reliability, the speed of employees in administrative management has been classified as good, seen from the ability and expertise in the use of technology in the office as a tool in the process of serving the community. Responsiveness, in serving the community, cannot yet be fully felt by the community, because officers in performing services are not in accordance with the right time and there are still some complaints from the community that cannot be responded quickly. Guarantees, there are still services that have not been guaranteed to be completed within the allotted time. Empathy, special treatment is still found for people who have kinship relations.